A Cross-Sectional Study of Premenopausal Women’s Attitude Toward Menopause going Through Hysterectomy from Khyber Teaching Hospital, Peshawar - Ambareen, Asma; Gul Bangash, Arzoo; Mazhar, Tayyaba; Nawsheen, Sania (Indus Journal of Bioscience Research, 2024)
Background: Women undergoing early menopause following premenopausal hysterectomy often experience significant fear and health challenges. Understanding their attitudes toward this transition is essential for providing effective healthcare tailored to their needs. Objective: This study aimed to assess the attitudes of women toward early menopause following premenopausal hysterectomy performed for gynecological or obstetric reasons. Methodology: The study was conducted at Khyber Teaching Hospital, Peshawar, from January to June 2024. Women aged 30–45 years who had not yet attained menopause but underwent premenopausal hysterectomy were included. Exclusion criteria included those on hormone replacement therapy (HRT). Data were collected through a semi-structured questionnaire with two sections: Section A recorded demographic details, while Section B assessed knowledge and attitudes. Data were analyzed using SPSS version 26, with associations evaluated via the Chi-square test (p ≤ 0.05). Results: Among 80 participants, the mean age was 39.3 ± 3.23 years. Most were multiparous (86.3%), and 55% reported a household income below 25,000 PKR. Poor knowledge about early menopause was observed in 55% of participants, while 22.5% showed good knowledge. Positive attitudes toward long-term complications were prevalent (86.3%), with 85% adopting preventive measures. Poor knowledge was significantly associated with lower income (p=0.024) and illiteracy (p=0.001). Multiparity showed no significant correlation with knowledge (p=0.304). Conclusion: Despite positive attitudes and proactive measures, knowledge gaps about early menopause were significant, particularly among less educated and low-income groups. Targeted educational programs are essential to bridge these gaps and enhance preparedness for early menopause.